The Influence of Work Discipline on Employee Performance at the Borong Subdistrict Office, Manggala District, Makassar City - Maryani Rizda Pristiani (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine and describe the influence of work discipline on employee performance in the Borong sub-district office, Manggala sub-district, Makassar city. The method used in this research is a mixed quantitative and qualitative method. Where quantitative methods are more dominant and qualitative methods are complementary to the data. The sample in this research consisted of ten people and the informants in this research were four people. The indicators of work discipline in this research are (1) attitude, (2) Norms, (3) Responsibility. The employee performance indicators in the research are (1) Quality, (2) Quantity, (3) Timeliness, (4) Effectiveness, (5) Independence. The results of the research conducted show that the influence of work discipline on employee performance has a positive value of 0.876 (87.6%) and a P value = 0.000. With a correlation value (R) of 0.947 which shows a very strong relationship between work discipline and employee performance. The determination value (R2) is 0.896 (89.6%). Shows that the contribution of work discipline in explaining variations in employee performance scores is 89.6%, while the remaining 10.4% is explained by other variables not examined in this research.